HUBUNGAN TINGKAT PENGETAHUAN OBAT GASTRITIS YANG DIIKLANKAN DI TELEVISI TERHADAP PERILAKU SWAMEDIKASI MASYARAKAT DI APOTEK SE-KECAMATAN BANGKINANG KOTA PROVINSI RIAU - Aryani, Fina; Aryani, Soufie; Muharni, Septi (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
Gastritis is a condition where the production of acid in the stomach can cause irritation. To treat gastritis, patients can do self-medication (self-medication). The factors that influence self-medication are sources of information such as advertisements on television. Self-medication behavior requires knowledge so that treatment is safe and rational. The purpose of this study was to determine the relationship between knowledge of gastritis medicine advertised on television and self-medication behavior in pharmacies in Bangkinang District, Riau Province. The type of research is observational, descriptive analytic method with cross sectional design and data collection simultaneously. Sampling was done by purposive sampling in order to obtain a total sample of 110 respondents who met the inclusion criteria. The results of the statistical test obtained a p value < 0.05, which means that there is a relationship between knowledge of gastritis medicine advertised on television and self-medication behavior in pharmacies throughout Bangkinang District, Riau Province.